Very Late-Onset Serious Chronic Adverse Effects After Radical Chemoradiotherapy for Anal Canal Cancer - Vitek, Pavel; Kubes, Jiri; Ondrova, Barbora; Haas, Alexandra (Journal of clinical medicine, 2025)
Radical chemoradiotherapy has been used as a frontline treatment for squamous cell cancer of the anus for the last 30-40 years. Considerable acute and chronic adverse effects have been observed following radiotherapy using 2D and 3D techniques. A case of very late-onset severe chronic toxicity in a patient 26 years after radiotherapy is presented. The patient underwent radical chemoradiotherapy for squamous anal cancer stage T3N3M0 in 1998. In the anal region, cumulative doses up to 77.6 Gy (including electron boost) were administered. Durable complete regression of the disease was achieved. Fourteen years after treatment, the patient developed vast fibroatrophy of the anus and perineum, progressing within the subsequent four years to necrosis and sphincter loss. Twenty years after treatment, the asymptomatic osteonecrotic foci in the left femur appeared on MRI scans. Despite two courses of hyperbaric oxygen treatment, the fibroatrophy and subsequent necrosis of soft tissues remained progressive, but the osteonecrosis was stable. Twenty-six years after treatment, the progressive changes induced symptomatic osteomyelitis of the ischium and pubic bone. The patient now requires permanent supportive treatment. The presented case is exceptional in the very late-onset typical chronic adverse effects developing after non-conformal radiotherapy administered at high doses as part of contemporary treatment protocols. There is little evidence regarding the late onset of chronic adverse effects, since the follow-up period is usually shorter than that of the case presented. Moreover, a significant portion of patients do not survive to reach the late-onset period of adverse effects. The presented case shows that there may be long-term survivors of anal cancer in the population who were treated with outdated techniques and who still carry a risk of late-onset severe, progressive adverse effects.